Indonesia’s Safeguarding of Human Rights to Achieve Sustainable Development Goals: Insights from Australia’s Experience - Andini, Orin Gusta; Muhammad Riyan Kachfi Boer (Journal of Sustainable Development and Regulatory Issues (JSDERI), 2025)
Indonesia has undertaken numerous initiatives to protect human rights through ratified national and international legal frameworks. However, challenges remain as violations of fundamental human rights persist. This article examines Indonesia's efforts to protect human rights through sustainable development and compares them with Australia's approach to achieving sustainable development goals (SDGs) by upholding human rights. The study employs a normative legal research method, utilizing statutory and case approaches. Primary and secondary data sources, including relevant human rights legislation, were analyzed qualitatively to address the research objectives. The findings indicate that Indonesia is committed to the SDGs and identified national targets aligned with Goal 16, emphasizing peace, justice, and strong institutions. While Indonesia and Australia face similar challenges in achieving the SDGs, Indonesia can draw lessons from Australia’s experience, particularly in strengthening the localization of SDGs and adopting objective success measures. Implementing data-driven evaluations of progress, gaps, and opportunities will enable Indonesia to formulate relevant policies and improve SDG outcomes. Adopting such measures is crucial for Indonesia to advance its human rights agenda and sustainable development efforts more effectively.